Molecular Characterization of Ancylostoma ceylanicum Kunitz-Type Serine Protease Inhibitor: Evidence for a Role in Hookworm-Associated Growth Delay - Chu, Daniel (American Society for Microbiology, 2004)
Hookworm infection is a major cause of iron deficiency anemia and malnutrition in developing countries. The Ancylostoma ceylanicum Kunitz-type inhibitor (AceKI) is a 7.9-kDa broad-spectrum inhibitor of trypsin, chymotrypsin, and pancreatic elastase that has previously been isolated from adult hookworms. Site-directed mutagenesis of the predicted P1 inhibitory reactive site amino acid confirmed the role of Met(26) in mediating inhibition of the three target serine proteases. By using reverse transcription-PCR, it was demonstrated that the level of AceKI gene expression increased following activation of third-stage larvae with serum and that the highest level of expression was reached in the adult stage of the parasite. Immunohistochemistry studies performed with polyclonal immunoglobulin G raised against recombinant AceKI showed that the inhibitor localized to the subcuticle of the adult hookworm, suggesting that it has a potential in vivo role in neutralizing intestinal proteases at the surface of the parasite. Immunization with recombinant AceKI was shown to confer partial protection against hookworm-associated growth delay without a measurable effect on anemia. Taken together, the data suggest that AceKI plays a role in the pathogenesis of hookworm-associated malnutrition and growth delay, perhaps through inhibition of nutrient absorption in infected hosts.